Tiotropium bromide - Lipson, David A (Dove Medical Press, 2006)
Therapy with bronchodilators forms the pharmacologic foundation of the treatment of patients with COPD. Bronchodilators can significantly lessen dyspnea, increase airflow, improve quality of life, and enhance exercise performance. While bronchodilators decrease airway resistance and lessen dynamic hyperinflation in patients with COPD, they have not been shown to alter the rate of decline in FEV(1) over time, or improve patient survival. Fairly recently, a long-acting, once-daily anticholinergic medication, tiotropium bromide, has been developed which may improve symptom management in COPD patients. This paper reviews anticholinergic pharmacologic therapy for patients with COPD focusing on tiotropium bromide, and discusses treatment strategies based on disease stage. It is important to recognize that while bronchodilators improve symptoms, a multimodality treatment approach including respiratory and rehabilitative therapy, nutrition services, psychosocial counseling, and surgical care, is often necessary for the best possible care of patients with COPD.